Sidman or statistics? - Iversen, Iver H (Journal of the experimental analysis of behavior, 2021)
Murray Sidman's statements regarding variability, experimental control, and generality are interwoven with examples from the literature on conditional discrimination. Sidman's position was that statistical inferences from group studies produce no information about the behavior of individual subjects and that statistical treatment of individual subject data masks variability which may represent conditions that are not controlled. Sidman's work on conditional discrimination provides excellent examples of how complex discriminations should be examined in detail with accuracy levels obtained for each type of discrimination within an experiment. Sidman made important contributions to the foundation of behavior analysis with extensive basic research as well as applications of methods and principles to clinical and educational settings.